Bacterial Extracellular Polymeric Substances Amplify Water Content Variability at the Pore Scale - Guo, Yi-Syuan; Furrer, Jessica M.; Kadilak, Andrea L.; Hinestroza, Hector F.; Gage, Daniel J.; Cho, Yong Ku; Shor, Leslie M. (Frontiers in Environmental Science, 2018)
The function of microbial communities in soil is inextricably linked with the complex physical, chemical and biological structure of the soil itself. Pore-scale water content controls the hydraulic connectivity of microbial communities and microbes’ access to aqueous and gaseous substrates. In turn, soil bacteria directly influence local moisture conditions through the secretion of extracellular polymeric substances (EPS). However, the effect of a soil’s physical geometry on EPS-mediated water retention is not well understood. In this study, we systematically measured the rate and extent of water evaporation from pore structures as a function of both EPS concentration and pore size. Three different chamber types were employed: (i) glass capillary tubes (1.2 mm pore diameter) to represent a uniform macropore geometry; (ii) emulated soil micromodels (pore widths ~ 10 µm to > 300 µm) to represent an aggregated sandy loam pore geometry; and (iii) microfluidic capillary arrays (uniform channels 20 µm wide) to represent a uniform micropore geometry. All chambers were initially saturated with dilute EPS solutions collected from stationary-phase Sinorhizobium meliloti cultures and then the infiltration of air was tracked over time. In the largest chambers, EPS concentration had no effect on the extent of evaporation or on the magnitude or variability of the evaporation rate. However, in the chambers with micropore-sized physical features, EPS concentration strongly influenced rate, extent, and variability of pore water evaporation. In micropores, higher EPS concentrations enhanced water retention and led to greater variability in pore-scale water distributions. In real soil, these phenomena could act together to promote the intermediate water contents associated with productive soil systems, and more variable pore-scale water distributions could increase microbial community diversity and the resiliency of soil systems.